Analysis of genetic polymorphisms for age-related macular degeneration (AMD) in Chinese Tujia ethnic minority group - Shengchun Liu; Mingxing Wu; Bianwen Zhang; Xiaojing Xiong; Hao Wang; Xiyuan Zhou (BMC Medical Genetics, 2019)
Abstract Background Age-related macular degeneration (AMD) can cause vision loss or blindness in elderly. The associations between single nucleotide polymorphism (SNP) and AMD in Chinese Tujia ethnic minority group are still unclear. Methods A total of 2122 Tujia volunteers were recruited and 197 of them were diagnosed with AMD (either dry or wet type).Then the blood specimens of these 197 AMD patients and 404 controls from the remaining 1925 normal Tujia volunteers were collected to detect the frequencies of 39 chosen SNPs. The Bonferroni method was used to correct the P values from the Fisher’s exact test. Results The mean age of the 197 AMD patients(113 males and 84 females) was 68.4197 years old. No significant differences in allelic and genotypic frequencies were found for all the 39 SNPs between the patients and controls. However, weak correlations between 10 SNPs (CFH rs1329428 TT genotype, CFH rs3753394 CC genotype and T allele, CFH rs1410996 AA genotype, CFH rs800292 AA genotype, CFH rs800292 A allele, VEGF rs833061 TT genotype and C allele, VEGF rs2010963 CG genotype, VEGFR2 rs1531289 TT genotype, ARMS2 rs10490924 TT genotype, KCTD10 rs238104 GC genotype, rs1531289 T allele and ARMS2 rs10490924 T allele) and AMD were shown. Conclusions The effects of 39 SNPs have found no associations with the morbidity of AMD in Chinese Tujia ethnic minority group.